Two Lexical Interpretations (brda bkrol) on the Lam rim chen mo - Dorjsuren, Burnee (Tibetan Studies, 2025)
The བྱང་ཆུབ་ལམ་རིམ་ཆེན་མོ།, or The Great Treatise on the Stages of the Path to Enlightenment (composed in 1402 by Tsong kha pa [1357–1419]), is one of the most influential religious and philosophical works in Tibetan Buddhism. It systematically presents the path to enlightenment of the beings of the three capacities. A vast corpus of literature—encompassing instructions, commentaries, manuals, invocations, recitations, prayers, poems, hymns, aphorisms, and praises—has emerged around this seminal text, primarily transmitted in the Tibetan language. Among these, particular significance is attached to the genre known as brda bkrol (pronounced da dol in Mongolian), or "word interpretation." This article examines brda bkrol of A kya yongs ‘dzin dbyangs can dga’ ba’i blo gros (ཨ་ཀྱ་ཡོངས་འཛིན་དབྱངས་ཅན་དགའ་བའི་བློ་གྲོས།, 1740–1827) and dpal mang paN+dita dkon mchog rgyal mtshan (དཔལ་མང་པཎྜིཏ་དཀོན་མཆོག་རྒྱལ་མཚན།(1764–1853). A kya yongs ’dzin dbyangs can dga’ ba’i blo gros’s work provides detailed explanations for over 650 terms and phrases, drawing from a wide range of canonical sources and oral traditions. In contrast, dpal mang paN+dita dkon mchog rgyal mtshan's work, while more concise, offers interpretations of over 150 key terms, making it an accessible yet valuable contribution to the field. These two commentaries focuses on clarifying and interpreting terms and expressions used in the Lam rim chen mo, serving as a vital tool for readers, scholars, translators, and dictionary compilers. Зонховын “Их бодь мөрийн зэрэг”-ийн хоёр зүйл дадол буюу дохионы тайлбарын тухай Хураангуй: Богд Зонховын (1357-1419) зохиосон “Их бодь мөрийн зэрэг” (тө. བྱང་ཆུབ་ལམ་རིམ་ཆེན་མོ།, 1402) бол буддын шашны гэгээрэлд хүрэх зам мөрийг гурван төрөлхтний замналаар тогтолцоотой өгүүлсэн шашин гүн ухааны алдартай сурвалж бичиг билээ. Тус бүтээлийн судлалтай холбоотой хөтөлбөр, тайлбар, үндэс дамжлага, оюун судалбар, уншлага, залбирал, шүлэг дуулал, сургаал, магтаал зэрэг олон бүтээл төвөд хэлээр уламжилж иржээ. Тэдгээрийн нэг бол “дохионы тайлбар” буюу дадол (тө. brda bkrol) юм. Дадолд нэр томьёо, оноосон нэр, санскрит үг, хуучирсан хэллэг, нутгийн аялгуу, хэлц хэллэг тэргүүтнээс түүвэрлэн тухайн зохиолд орсон дарааллаар тайлбарласан байдаг. Тус өгүүлэлд Ажа ёнзин Янжингавилодой (1740-1827) болон Балман Гончигжалцан (1764-1853) нарын бичсэн дадолыг харьцуулна. Ажа ёнзин Янжингавилодой 650 гаруй үг хэллэгийг олон сурвалж бичиг, аман мэдээ ашиглаж дэлгэрэнгүй тайлбарлажээ. Балман бандида Гончигжалцангийнх хураангуй, 150 гаруй үг хэллэгийг хамарч байна. Энэхүү хоёр бүтээл нь “Их бодь мөрийн зэрэг”-ийг уншиж судлах, орчуулах төдийгүй толь зүйч нарт чухал хэрэглэгдэхүүн, гарын авлага болсоор ирсэн байна. Түлхүүр үг: “Их бодь мөрийн зэрэг” дадол, Ажа ёнзин Янжингавилодойн дадол, Балман Гончигжалцангийн дадол